Implementation Of School Educational Personnel Archives Management At Muhammadiyah Bangkinang High School - Pratiwi, Arvina; Setyaningsih, Rini; Irawati, Irawati (EL-EMIR Institute, 2024)
This research aims to explore 1) how archives are lent, 2) how archives are maintained, and 3) how archives are stored at SMA Muhammadiyah Bangkinang Kota. This research is qualitative with descriptive methods. Respondents included school principals, heads of school administration, administrative staff and teachers. The object of the research is archive management by administrative staff at SMA Muhammadiyah Bangkinang Kota. The research results show that 1) archival lending has been implemented well, but archival borrowing is still not optimal. The party authorized to retrieve archives at Bangkinang City Muhammadiyah High School is the head of the school administration and administrative staff, but this rule is conveyed verbally. 2) Archive maintenance is carried out by arranging the storage space so that the archives remain dry and bright, and archival documents are arranged loosely in filing cabinets so that air can enter. The school also has anti-smoking regulations to keep records safe. However, there are problems with storage facilities. 3) Archive storage uses a subject system, namely managing archives based on topics. Obstacles include a lack of special storage space and inadequate facilities.